Lactate Facilitates Pancreatic Repair Following Acute Pancreatitis by Promoting Reparative Macrophage PolarizationSummary - Jing Jiang; Ruiyan Wang; Pengli Song; Qi Peng; Xuerui Jin; Bin Li; Jianbo Ni; Jie Shen; Jingpiao Bao; Zengkai Wu; Xiaolu Ge; Xingpeng Wang; et al. (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: During acute pancreatitis (AP), glycolysis is enhanced. The upregulation of glycolysis increases the level of metabolite lactate. Lactate has been shown to facilitate tissue repair across various pathologic conditions. However, its role in the recovery following AP remains unclear. This study aims to explore the role of lactate in the regenerative processes following AP and to elucidate its underlying molecular mechanisms. Methods: The caerulein-induced recovery AP model was established using wild-type and 6-Phosphofructo-2-Kinase/Fructose-2,6-Biphosphatase 3 (Pfkfb3) heterozygous mice. Pancreatic repair was evaluated histologically, whereas lactate levels and inflammatory markers were measured serologically. Macrophages were isolated from pancreatic tissue using fluorescence-activated cell sorting for mRNA sequencing to identify phenotypes. In ex vivo, macrophages were indirectly co-cultured with inflammatory acinar, and the effect of lactate on macrophage phenotype were investigated through immunoprecipitation, fluorescence analysis, and Western blotting. Results: We first found that exogenous lactate administration promoted pancreatic repair, whereas Pfkfb3 deficiency lowered lactate levels and ultimately delayed pancreatic repair. Mechanistically, lactate altered macrophage phenotype during recovery after AP, by reducing the proportion of pro-inflammatory macrophages and increasing the percentage of reparative macrophages. In the indirectly co-cultured macrophage, lactate increased lactylation levels and enhanced repair gene expression. Treatment with AZD3965, a chemical inhibitor of lactate transportation, blocked the effects on lactylation and gene expression. Besides, lactate repressed the JAK2-STAT1 pathway via GPR132 receptor, thereby suppressing the expression of pro-inflammatory genes. Conclusions: Lactate facilitates pancreatic repair by promoting reparative macrophage polarization, achieved through promoting lactylation and inhibiting JAK2-STAT1 signaling. This phenotypic shift alleviates inflammation and facilitates tissue recovery, highlighting a potential therapeutic approach for AP.